The effect of digital leadership and innovation management for incumbent telecommunication company in the digital disruptive era - W Wasono, Leonardus; Furinto, Asnan (International Journal of Engineering and Technology, 2018)
Digital technology drives the changing more exponential across all industry. Telecommunication is one of industries that having significant impact of digital disruption. Thus, it become the issue for incumbent telecommunication company to sustain their future business. The incumbents require to re-inventing its strategy to anticipate the rapid changing in digital disruption. Two big challenges for incumbents are how to take the opportunity in digital disruption through innovation management? and how to accelerate internal digital transformation lead by digital leadership capability. This study aims to examine the effect of digital leadership and innovation management for incumbent telecommunication company in Indonesia in facing the digital disruption and transform into digital telco. This study uses quantitative method in incumbent telecommunication company in Indonesia with sample of 100 respondents. The statistical test used is Partial Least Square (PLS). The result of hypothesis testing found that both digital leadership and innovation management effect to sustainable competitive advantage, where the digital leadership have a greater influence in driving innovation management. This research has implication for incumbent telecommunication company in Indonesia in its effort to transform into digital telco and increase sustainable competitive advantage in disruptive era through strengthening the digital leadership and innovation management.
Keywords: Digital Leadership; Innovation Management; Digital Disruptive.